Re-examining infrastructure-led growth theory: The role of telecommunication on growth in Indonesia - Aisyah Hashinatun Nithosyi; Mahrus Lutfi Adi Kurniawan; Jihad Lukis Panjawa (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2026)
This study re-examines the infrastructure-based growth theory by assessing the contribution of telecommunications to regional economic growth in Indonesia. Panel data from 34 provinces during the period 2018–2022 were analyzed using panel data regression; Chow and Hausman tests selected the fixed effects model. The dependent variable is the log of gross regional domestic product, while the independent variables include foreign direct investment, gross fixed capital formation, labor force, number of base transceiver stations, and telecommunications network performance. The results show that base transceiver stations, telecommunications network performance, and gross fixed capital formation have a positive and significant effect, while foreign direct investment has a negative effect and labor force is insignificant. These findings confirm the importance of digital infrastructure in increasing productivity and market integration, but at the same time highlight the connectivity gap between provinces. Policies need to prioritize improving network quality and equitable development of telecommunications infrastructure in disadvantaged areas.